Bridging microscale to macroscale mechanical property measurements of FeCrAl alloys by crystal plasticity modeling. (June 2023) - Gong, Mingyu; Xie, Dongyue; Sun, Tianyi; Zhang, Xinghang; Shao, Lin; Wang, Jian
Highlights: The intrinsic frictional resistance associated with 110<111> and 112<111> slip systems were measured by in-situ micromechanical testing on unirradiated/irradiated FeCrAl alloys at 25-500 °C. Deformation-induced dislocations and radiation-induced defects result in obvious hardening at room temperature but weakened at high temperature. Both high temperature and radiation-induced defects facilitate dislocation multiplication, triggering large hardening rate. A microstructure- and temperature-dependent crystal plasticity model is employed to bridge microscale to macroscale mechanical property measurements of FeCrAl alloys. Abstract: FeCrAl alloys are candidates for accident tolerant fuel cladding of light water reactors. In this work, a microstructure- and temperature-dependent crystal plasticity model is employed to bridge microscale to macroscale mechanical property measurements of FeCrAl alloys. With the visco-plastic self-consistent (VPSC) polycrystal plasticity framework, a mechanism-based single crystal plasticity (MSCP) model adopts the Arrhenius type rate equation to describe the dependence of the critical resolved shear stress for dislocation slips on their temperature-dependent intrinsic frictional resistance and the microstructure-dependent irradiation hardening. The intrinsic frictional resistance associated with 110<111> and 112<111> slip systems were measured by in-situ micromechanical testing on unirradiated/irradiated samples at 25-500 °C. The irradiation hardening is estimated by the Bacon-Kocks-Scattergood (BKS) model with density and size of radiation-induced defects measured from microstructural characterization. Several features associated with thermo-mechanical behavior of unirradiated/irradiated polycrystalline FeCrAl alloys are captured. High density of deformation-induced dislocations and radiation-induced defects results in obvious hardening at room temperature, which is weakened at high temperature, and facilitates damage evolution during deformation. Moreover, both high temperature and radiation-induced defects, which facilitate dislocation multiplication, trigger large hardening rate. The proposed method together with application of accelerator-based ion irradiation technique is a surrogate approach to simulate neutron damage, improving the efficiency associated with evaluation of mechanical properties of FeCrAl alloys exposed to temperature, stress and radiation conditions. Graphical Abstract: Image, graphical abstract